ANALISIS KEJADIAN STUNTING DI PROVINSI NUSA TENGGARA BARAT MENGGUNAKAN METODE PATH ANALYSIS - Assani, Moh. Yushi; Kusrini Kusrini; Kusnawi Kusnawi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
Stunting is a problem in many developing countries, including Indonesia. Toddlers are a critical period for a child's development, this period can determine the child's level of development in the future. Not preparing yourself well at this stage can cause growth and development problems in children, including delays in growth and development. Stunting can cause suboptimal brain development and delays in motor development in children. Based on the results of the analysis, it is known that there is a direct effect between the husband's age on the baby's birth weight with a value of -0.234. Apart from that, the husband's smoking habit also has a direct effect on the baby's birth weight with a value of -0.176. Overall, the results of the path analysis show that husband's characteristics such as age, education, occupation, and smoking habits have a significant effect on the baby's birth weight. Husband's age is negatively correlated, while education and employment are positively correlated. These results need to be followed up with intervention and education for prospective fathers to improve the health of mothers and babies.